Respons Infiltrasi Kawasan Gunung Sasak terhadap Variabilitas Tutupan Vegetasi - Humairo Saidah; M. Bagus Budianto; Anid Supriyadi; Sri Handayani Astuti (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
Groundwater availability in catchment areas is influenced by the soil capacity to infiltrate rainfall, which is related to vegetation cover conditions. This study aimed to analyze the infiltration response to variations in vegetation density in the Gunung Sasak region, West Lombok. Field measurements were conducted at six sites representing different vegetation-cover densities using a double-ring infiltrometer following SNI 7752:2012. Infiltration data were analyzed descriptively, comparatively, and through linear regression, then related to soil physical properties. The results showed that dense vegetation produced higher infiltration rates than open land or sparsely vegetated areas. The densest forest site recorded an initial infiltration rate of 48 cm/hour, an average infiltration rate of 15.600 cm/hour, and an infiltration capacity of 8.0 cm/hour. Vegetation density showed strong to very strong correlations with infiltration, with R² values of 0.7285–0.8513. Porosity was positively associated with infiltration (R² 0.9126), whereas bulk density showed a negative relationship (R² 0.9243)